Three-dimensional virtual microstructure generation of porous polycrystalline ceramics. Issue 17 (1st December 2019) - Naderi, Sadjad; Dean, Julian S.; Zhang, Mingzhong
Abstract: Various numerical methods have been recently employed to model microstructure of ceramics with different level of accuracy. The simplicity of the models based on regular morphologies results in a low computational cost, but these methods produce less realistic geometries with lower precision. Additional methods are able to reconstruct irregular structures by simulating the grain-growth kinetics but are restricted due to their high computational cost and complexity. In this paper, an innovative approach is proposed to replicate a three-dimensional (3D) complex microstructure with a low computational cost and the realistic features for porous polycrystalline ceramics. We present a package, written in MATLAB, that develops upon the basic Voronoi tessellation method for representing realistic microstructures to describe the evolution during the solid-state sintering process. The method is based on a cohesive prism that links the interconnect cells and thus simulates the neck formation. Spline surfaces are employed to represent more realistic features. The method efficiently controls shape and size and is able to reconstruct a wide range of microstructures composed of grains, grain boundaries, interconnected (open) and isolated (closed) pores. The numerical input values can be extracted from 2D imaging of real polished surfaces and through theoretical analysis. The capability of the method to replicate different structural properties is tested using some examples with various configurations. Graphical abstract: Image 1 Highlights: Employment of a geometric analogy between Coble's model and Voronoi cells. Fitting spline surfaces to generate more realistic geometry. Simulation of neck formation. Effective size and shape control. Modelling open and closed porosity.